A survey of chronic pain in China. Issue 1 (1st January 2020) - Yongjun, Zheng; Tingjie, Zhang; Xiaoqiu, Yang; Zhiying, Feng; Feng, Qiu; Guangke, Xin; Jinfeng, Liu; Fachuan, Nie; Xiaohong, Jin; Yanqing, Liu
ABSTRACT: There is an extensive body of research about chronic pain and treatment in developed countries. In contrast there is a lack of research on this topic in developing countries including China. This study was aimed to estimate the prevalence of chronic pain in different regions of China. Data on pain and its treatment were collected from 9357 participants using questionnaires and telephone-based interviews, from 31 regions of China. Gathered data were then coded into electronic data acquisition system and descriptive and inferential statistical analysis was performed. Out of 9298 participants, the ratio of chronic pain was 31.54% with the proportion of male having chronic pain (33.86%) was higher than that of female (29.53%). The average age of participants with pain (45.02 ± 15.07 years) was higher than free-pain participants (36.19 ± 11.12 years). There were also significant differences between groups in occupation, education levels, and illness history. Proportion of patients with pain duration of 1 year was 12.104%, between 1 and 5 years was 60%, and over 10 years was 10.74%. There were 63.9% of patients with moderate pain and 36.1% with severe pain. About 43.042% of patients thought that pain resulted in sleep disorder, 38.99% thought that it causes anxiety, and about 33% thought depression and irritable bowel was the result of their pain. For the chronic pain, more than half of patients used naprapathy, cupping, and other physical therapies. Up to 2016, the ratio of pain incidence was over 30% in China. The location of pain was focused on back and upper limb. There has been a lack of proper treatment. Patients with pain had obvious economic burden, and their quality of life and psychology were significantly affected.